The spirit of stone : 101 practical & creative stonescaping ideas for your garden - Johnsen, Jan (St. Lynn's Press, 2017)
"... guide to creative and practical uses for stone and gravel in the landscape: rock gardens, steps, paths, benches, and more. Stone's durability, coupled with its sustainable uses, make it especially appealing to homeowners looking for innovative ideas for conserving water. A special chapter is devoted to plants and stones to showcase how these two complement each other in a garden."--Amazon.com.